PERKAWINAN DI BAWAH UMUR AKIBAT SANKSI LAMBAT MULAK MARGANDAK DI KAB. PADANG LAWAS UTARA PERSPEKTIFUNDANG-UNDANG NO 16 TAHUN 2019 - Ritonga, Nasrul (Khulasah : Islamic Studies Journal, 2024)
This research discusses underage marriage as a result of sanctions that are slowly starting to fade in the district. Padang Lawas Utara perspective law no. 16 of 2019. The tradition of marrying off girls due to late onset of margandak is a tradition that has been passed down from generation to generation by this community. The problem formulation in this thesis is: what are the factors that encourage people to marry off their daughters because they are slow to marry, how is the implementation of the customary sanctions for marrying off their daughters because they are late to marry in Padang Lawas Uatara District and what is the analysis of Law No. 16 of 2019 concerning sanctions the margandak started slowly. The research used is field research (file research), which starts from data collection: observation, interviews, documentation both primary: actors and community figures and secondary: literature and from community leaders who know about related problems. These data will be explored in literature that is deemed relevant. And analyzed using qualitative descriptive techniques. The results of the factors that are the cause of the tradition of immediately marrying off girls are still implemented due to the slow start of margandak in the district. North Padang Lawas is: because of tradition (custom), it is a disgrace to the family, economy, education. Implementation of the tradition of immediately marrying girls because margandak is slow when a girl returns home for a long time with a boy, and her parents no longer accept the presence of a girl because they consider it to be a very big disgrace, then that's when the wedding takes place and it is a customary sanction. And this tradition never has an age limit as long as he reaches puberty. Government Regulation Number 16 of 2019 concerning Underage Marriage due to the slow start to the validity of the marriage procedure is invalid or not accepted by applicable law because it does not comply with existing procedures.